“La experimentación como estrategia didáctica para el proceso de enseñanza aprendizaje en las Ciencias Naturales de los cuartos años de educación básica“ - Fabara Herrera, Jhesenia Silvana (2023)
The current inquiry project has the objective of determining experimentation as a valid strategy in the teaching-learning process, given that, it is pragmatic in Natural Sciences subject in fourth year of basic education at “Lic. Jaime Andrade Fabara” school to achieve meaningful learning results. This project was built throughout an quali-quantitative approach, which seeks to analyze and garner outstanding information because it enables to get involved in the study problem context and acquire numerical and quantifiable data by means of the survey application to fourth year students. Experimentation as a didactic alternative in Natural Sciences has a wide value since though this, learning of this area´s content is encouraged and facilitated, that is why we were motivated to carry out this research project, then teaching Natural Sciences must leave behind its traditionalist sense and conceive objectively knowledge where is the student who develops meaningful learning. It is stablished conclusion and recommendations to improve students’ performance through experimentation to facilitate learning in the Natural Sciences area and to dabble into innovate changes in education, that are accomplished under professor’s guide who are mediators.